Examining the Needs of MEB Public Schools for Special Education - Çoban, Firdes; Ceylan, Müyesser (Mimbar Sekolah Dasar, 2023)
Individuals start their educational journey with their differences, and it is important to plan education in accordance with the differences. Within the scope of examining the needs of MEB Public Schools for Special Education, the purpose of the study is to determine and examine the needs necessary for the continuity of the education-training process under the umbrella of the “Education System”. The study was carried out in a special education school. The data of the study was collected with a “Semi-Structured Interview Form” in the “Case Study” design of the qualitative research method. The findings obtained from the participants were classified under several headings such as special education teachers’ professional competence and personal rights, students’ educational needs and services offered to them, the location and structural condition of the school; the budget and financial needs of the school, the relations between the school and the family, the school and environment, etc. . In line with the purpose of the study, comparisons were made within the theoretical framework, and suggestions were made. The results of the study related to the needs show that the special education schools, special education students and their families, and even the social environment factor should be considered as a whole.